The Improvement of Students’ Ability in Writing Procedure Text Through Picture Series - Gendroyono Gendroyono (Jurnal Pendidikan Indonesia, 2021)
This research study on improving the students’ ability in writing procedure text through picture series is action research. This is categorized as action research since there is a self-reflective, critical, and systematic approach that the researcher does to identify a problematic situation as a way of improvement and changes in educational practice. In doing this action research, the researcher considers phases that involve each cycle. Those are planning, action, observation, and reflection.  Every phase is done based on the researcher’s ideas on the research. This study is aimed at exploring the improvement of the teaching and learning process writing procedure text using picture series. It is also intended to identify the improvement of students’ ability in writing procedure text using picture series. Based on the research findings and the discussions in section four, some conclusions can be drawn as follows: the use of picture series promotes the improvement of students’ ability in writing procedure text and can elevate the students’ interest or motivation in the classroom. Picture series is very good in providing the idea for the students to write. The students’ works are also more persistent to the idea as compared to when not using the picture series. The pictures also attract more attention from the students and motivate students to get involved in the classroom interaction with the teacher and among themselves. For the detailed works of the students, the use of appropriate diction and the improvement of vocabulary mastery is also the effect of the use of the picture series. Further, the changes of the pictures in every meeting make the students remain interested in participating in the teaching and learning process because they do not feel bored.